Thermodynamic analysis of the system Na2O-K2O-CaO-Al2O3 -SiO2 -H2O-F2 O)1 : Stability of fluorine-bearing minerals in felsic igneous suites - Dolejš D.; Baker D.R. (My University, 2004)
Thermodynamic analysis of the system Na2O-K2O-CaO-Al2O3-SiO2-H2O-F2O−1 provides phase equilibria and solidus compatibilities of rock-forming silicates and fluorides in evolved granitic systems and associated hydrothermal processes. The interaction of fluorine with aluminosilicate melts and solids corresponds to progressive fluorination of their constituent oxides by the thermodynamic component F2O−1. The chemical potential μ(F2O−1) buffered by reaction of the type: MOn/2 (s)+n/2 [F2O−1]=MFn (s, g) where M=K, Na, Ca, Al, Si, explains the sequential formation of fluorides: carobbiite, villiaumite, fluorite, AlF3, SiF4 as well as the common coexistence of alkali- and alkali-earth fluorides with rock-forming aluminosilicates. Formation of fluorine-bearing minerals first starts in peralkaline silica-undersaturated, proceeds in peraluminous silica-oversaturated compositions and causes progressive destabilization of nepheline, albite and quartz, in favour of villiaumite, cryolite, topaz, chiolite. Additionally, it implies the increase of buffered fluorine solubilities in silicate melts or aqueous fluids from peralkaline silica-undersaturated to peraluminous silica-oversaturated environments. Subsolidus equilibria reveal several incompatibilities: (i) topaz is unstable with nepheline or villiaumite; (ii) chiolite is not compatible with albite because it only occurs only at very high F2O−1 levels. The stability of topaz, fluorite, cryolite and villiaumite in natural felsic systems is related to their peralkalinity (peraluminosity), calcia and silica activity, and linked by corresponding chemical potentials to rock-forming mineral buffers. Villiaumite is stable in strongly peralkaline and Ca-poor compositions (An<0.001). Similarly, cryolite stability requires coexistence with nearly-pure albite (An<2). Granitic rocks with Ca-bearing plagioclase (An>5) saturate with topaz or fluorite. Crystallization of topaz is restricted to peraluminous conditions, consistent with the presence of Li-micas or anhydrous aluminosilicates (cordierite, garnet, andalusite). Fluorite is predicted to be stable in peraluminous biotite granites, amphibole-, clinopyroxene- or titanite-bearing calc-alkaline suites as well as in peralkaline granitic and syenitic rocks. Fluorine concentrations in felsic melts buffered by the coexistence of F-bearing minerals and feldspars increase from peralkaline through metaluminous to mildly peraluminous compositions. At low-temperature conditions, the hydrothermal evolution of peraluminous granitic and greisen systems is controlled by white mica-feldspar-fluoride equilibria. With decreasing temperature, topaz gradually breaks down via: (i) (OH)F−1 substitution and fluorine transfer to fluorite by decalcification of plagioclase below 600 °C, (ii) formation of muscovite and additional fluorite at 475–315 °C, and (iii) formation of paragonite and cryolite, consuming F-rich topaz and albite below 315 °C. These equilibria explain the absence of magmatic fluorite in Ca-bearing topaz granitic rocks; its abundance in hydrothermal rocks is due to: (i) closed-system defluorination of topaz, (ii) open-system decalcification of plagioclase or (iii) hydrolytic alteration. These results provide a complete framework for the investigation of fluorine-bearing mineral stabilities in felsic igneous suites.